2016
DOI: 10.1097/md.0000000000003226
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Associated Factors of Periodontitis According to Fasting Plasma Glucose in the Korean Adults

Abstract: Although the relationship between diabetes and periodontitis is well established, the association between periodontitis and prediabetes has been investigated less extensively. Furthermore, there has been little research on the prevalence of periodontitis among individuals with prediabetes and diabetes as well as in the overall population using nationally representative data.Among 12,406 adults (≥19 years’ old) who participated in the 2012–2013 Korea National Health and Nutrition Examination Survey, a total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 29 publications
(29 reference statements)
3
29
2
1
Order By: Relevance
“…Total of 87% of smokers and 97% of diabetics had periodontitis similar to previous studies. 1,21,25 The association of periodontitis was found to be statistically significant with tobacco smoking, diabetes, hypertension and age but not with sex and family history of diabetes (Table 1, 3). Higher age predicted greater incidence of periodontal disease, however no difference in the proportion of periodontal disease was seen in male and female similar to previous studies.…”
Section: Discussionmentioning
confidence: 94%
“…Total of 87% of smokers and 97% of diabetics had periodontitis similar to previous studies. 1,21,25 The association of periodontitis was found to be statistically significant with tobacco smoking, diabetes, hypertension and age but not with sex and family history of diabetes (Table 1, 3). Higher age predicted greater incidence of periodontal disease, however no difference in the proportion of periodontal disease was seen in male and female similar to previous studies.…”
Section: Discussionmentioning
confidence: 94%
“…Periodontitis and malocclusion along with caries are significant public oral diseases with extremely high incidence rates. Epidemiologic studies show that more than 50% of adults suffer from periodontitis and severe periodontitis is estimated to occur in approximately 5-20% of adults worldwide (1)(2)(3). The prevalence of malocclusion among children is also more than 50%.…”
Section: Introductionmentioning
confidence: 99%
“…Tooth loss can substantially impair one's quality of life, causing limited chewing ability, poor dietary intake and functional disorders [1]. Research has shown diabetes and cardiovascular diseases to associate with oral health and tooth loss [2][3][4][5], and elevated glucose levels with common periodontal disease [6][7][8]. Similar finding has been reported between glucose concentration and the number of teeth [8].…”
Section: Introductionmentioning
confidence: 62%
“…Studies have suggested a bidirectional connection between, for example, diabetes and periodontal disease (a chronic inflammatory condition of supporting tissues of the teeth); periodontal disease is a complication of diabetes that plays an important role in poorly controlled diabetes [19]. Moreover, recent studies have reported an association between impaired glucose metabolism and periodontal disease [6,8].…”
Section: Discussionmentioning
confidence: 99%